Aplicação de um secador de leito fluidizado assistido por aquecimento infravermelho para o beneficiamento de pólen apícola - Borel, Lidja Dahiane Menezes Santos (2014)
In view of the increasing demand for natural products, bee pollen has received special attention due to the high availability of bioactive compounds in their chemical composition, which make it a product with high added value. Pollen grains have high moisture content, thus requiring to be submitted to a drying process, which is usually made naturally or in ovens with low processing capacity and difficulties to achieve quality standards. Within this context, o objective of this work was to study the application of a fluidized bed dryer assisted by an alternative energy source, such as the infrared radiation, for the processing of bee pollen. For this purpose, specific studies on different strategies drying were performed , through an experimental approach of aspects related to momentum, heat and mass transfer, energy consumption of the equipment and product quality. Grains of pollen in nature, from coconut (Cocos nucifera L.), with initial moisture ranging from 0.21 to 0.30 wb, and whose physical characterization was made via sieving, image analysis and permeametry, were used. The fluid dynamics behavior of beds filled with pollen grains was analysed at different loads (100 to 1800 g), different particle diameters and different moisture contents (7, 13 and 21% wb). The conventional fluidized bed drying was conducted with an initial load of 500 g under conditions of minimum fluidization and drying air temperatures of 35, 45 and 55°C. In order to evaluate the band intensity and the isolated effect of the infrared radiation (IR) to be applied during the hybrid drying, the IR drying kinetics of pollen was studied exposing a monolayer of particles to radiation intensities (IR) of 100, 400 and 700 W/m2 . The hybrid drying, combining the fluidization of particles and the IR heating, was performed with IR 100, 400 and 700 W/m2 without heating (Tair = 25 ° C) and heating the air (Tair = 45 ° C). During the process, energy consumption and the chromatic coordinates (L*, a*, b*) of the material were monitored. The drying of pollen grains, in all techniques investigated, was governed by the internal mass diffusion. The ten-terms solution of the second Fick’s law of diffusion was used to describe the drying kinetics of the material in the period of decreasing rate. The effective diffusivities obtained by applying radiation intensities of 100, 400 and 700 W/m2 to the bed of particles percolated by unheated air were in the range 3.1 to 3.98 x 10-11 m 2 /s. By comparing the results obtained for conventional and hybrid drying under conditions in which the material has reached the same temperature it was found an increase in Deff of about 30%, indicating an enhancement in the rate of mass transfer due to the application of IR heating in fluidized bed drying, what led to the reduction of energy consumption by 51%. The analysis of the colorimetric parameters in dehydrated pollen indicated the occurrence of browning reactions when IR radiation is applied alone for drying the material in a thin layer. However, the synergy between the IR heating and the cooling effect associated to the fluidizing air flow during the combined drying has contributed to maintain the color attributes as well as to preserve total carotenoids and betacarotene in the dehydrated bee-pollen.